Phenobarbitone induced steven johnson syndrome (SJS) Case report (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
IntroductionAdverse drug reactions (ADRs) are one of the leading causes of death in hospitalized patients. ADR is a response to a drug which is noxious, unintended and occurs at doses normally used in human for prophylaxis and treatment. Steven Johnson syndrome is an immune complex mediated hypersensitivity complex that typically involves the skin and mucous membranes. Steven Johnson syndrome and toxic epidermal necrolysis are rare (TEN 90% SJS less than 10% body surface area detachment) but life threatening cutaneous adverse drug reactions. Drugs like antiepileptics (Phenobarbitone, phenytoin, lamotrigine), antibiotics (penicillin, cephalosporins, sulphonamides) anti gout drug allopurinol are considered as one of the most common causative factor for these serious ADRs.DiscussionA four year old girl, known epileptic for the last two years, has generalized idiopathic epilepsy. She had been on Sodium Valproate and well controlled. The mother stopped the Valproate having been seizure free for two years .Two weeks later she had a generalized seizure lasting for ten minutes. The mother consulted some other doctor who prescribed Phenobarbitone 20 mg twice daily. Two weeks later she developed a skin rash on the face which spread to the trunk, upper and lower limbs and lastly the mucous membrane of the mouth and genitalia. The rash was very itchy. She also complained of inability to swallow and burning micturition due to genital ulcers. She was admitted to pediatric intensive care unit (PICU) in tertiary care hospital.  The symptomatic and supportive treatment with corticosteroids and liquid paraffin was given for the initial management of SJS. Patient was discharged after 24days treatment.ConclusionBy the withdrawal of the drug, the condition of the patient was improved. So the drug withdrawal is the first line for management of drug induced Steven Johnson syndrome.